Synergistic action of an Aspergillus (hemi-)cellulolytic consortium on sugarcane bagasse saccharification - de Oliveira Rodrigues, Patrísia (2017)
This study evaluated the synergistic efficiency of crude enzymatic extracts (CEE) produced by fungal strains Aspergillus fumigatus SCBM6 (AFE) and Aspergillus niger SCBM1 (ANE) in the hydrolysis of alkali pretreated sugarcane bagasse (2% NaOH (w v−1), ∼100 °C, 4 h and liquid-to-solid ratio of 25 (v w−1)). CEEs were produced by solid-state fermentation (SSF) and presented high concentration of β-glucosidase (AFE = 78.4 U g−1 and ANE = 43.02 U g−1), β-xylosidase (ANE = 78.0 U g−1) and xylanase (AFE = 1774.5 U g−1 and ANE = 3289.6 U g−1). A 24 full design of experiments was used to optimize the hydrolysis of pretreated bagasse as a function of time, temperature, amount of pretreated bagasse and AFE-to-ANE ratio. After hydrolysis optimization, the maximum concentration of total reducing sugars (TRS) was 21.68 g L−1. It was also noticed a significant production of xylose (135.59 mg) and arabinose (58.10 mg) per gram of hemicelluloses and a slight production of glucose (20.18 mg) per gram of cellulose. As fungi consortium were excellent producers of hemicellulases, it is suggested that they could be used for pentoses saccharification and production of ethanol via C-5 fermentation, xylitol, biopolymers, among other bioproducts.